The Effect of Using Talaqqi and Wahdah Methods Against Students' Ability to Memorize Al-Qur'an (Basic Education Level) - Parlaungan, Parlaungan; Hafsah, Hafsah; OK, Azizah Hanum (Jurnal Basicedu, 2022)
This study aims to determine the effect of using the talaqqi and wahdah methods on the ability to memorize the Qur'an of elementary age students. This study uses a quantitative approach with a quasi-experimental method. The research population was 104 students, which were used as research samples totaling 52 students. The results of this study conclude that (1) there is an effect of the talaqqi method on the ability to memorize the Qur'an of elementary age students with a result of 71%, (2) there is an effect of the wahdah method on the ability of memorizing the Koran of elementary age students with the results 73%, (3) there is an effect of talaqqi and wahdah methods on the ability to memorize the Qur'an of elementary age students. Based on these results, it is known that the use of the wahdah method is 2% superior to the talaqqi method on students' ability to memorize the Qur'an.